Is the convergence insufficiency symptom survey applicable to elderly individuals? - Saeid Abdi; Haleh Kangari; Saeed Rahmani; Alireza Akbarzadeh Baghban; Zahra Kamary Rad (BMC Ophthalmology)
Abstract Background The psychometric properties of the Convergence Insufficiency Symptom Survey (CISS) have been previously determined across the younger adult population. This study investigated the psychometric properties of the CISS in presbyopic adults via classical and Rasch analysis. Methods A total of 100 presbyopic individuals (40–60 years) were selected with far and near acuity of 20/20 with their habitual spectacles; 50 had convergence insufficiency and 50 had normal binocular vision. Refraction, cover test, near point of convergence, and positive fusional ranges were examined. The Persian translated CISS was administered twice, once in the first session and 7 to 14 days later. Classical and Rasch analyses were conducted. Results The mean ages and gender ratios in the CI group and normal group were 49.70 ± 5.96 and 49.82 ± 5.64 years with a 50% female distribution among individuals. The mean CISS scores for presbyopes with CI and normal groups were 19.24 ± 5.33 and 13.26 ± 3.53 respectively (p < 0.001). Effective discrimination was achieved with a score greater than 15, yielding a sensitivity of 72%, a specificity of 69%, and an Area Under the Curve (AUC) of 0.813. For internal consistency, Cronbach’s α coefficient was 0.82. For test-retest reliability in CISS scores, ICC was 0.91 (confidence interval 0.88–0.93) with the 95% limits of agreement in CI group being − 3.91 to 2.59. The Rasch analysis demonstrated a satisfactory model fit, as all items had infit and outfit mean square values ranging between 0.6 and 1.4. The measurement precision was good, with a person separation value of 2.30. Additionally, the first contrast eigenvalue of 2.34 and a raw variance of less than 50% indicated multidimensionality. The CI group reported headaches (item 3) more frequently than the normal binocular vision group did. However, eye discomfort scores (item 10) were similar for both groups. Conclusions The CISS is a valid and reliable tool for assessing the symptoms in presbyopic adults. However, due to this survey’s multidimensionality, we recommend additional objective examinations in presbyopic adults with CI.